Tracing the Spatial Patterns of Innovation Determinants in Regional Economic Performance - Alicja Olejnik; Agata Zȯĺtaszek (Comparative Economic Research. Central and Eastern Europe, 2020)
In this paper, we investigate innovation factors and their role in regional economic performance for a sample of 261 EU NUTS 2 regions over the period 2009-2012. In our study, we identify regions with spillover as well as drain effects of innovation factors on economic performance. The spatial analysis indicates that both regional in- novativeness and regional development are strongly determined by the region's location and "neighbourhood", with severe consequences for Central and Eastern Europe. We assessed the impact of innovation factors and their spatial counterparts on economic performance using a spatial Durbin panel model. The model is designed to test the existence and strength of the country-effect of innovativeness on the level of regional economic status. This allows for controlling the country-specific socio-economic factors, without reducing the number of degrees of freedom. Our model shows that regions benefit economically from their locational spillovers in terms of social capital. However, the decomposition of R&D expenditures revealed competition effect between internal R&D and external technology acquisition, favouring in-house over outsourced research.
Keywords: O30; O33; C21; C23; R12; 330; regional innovation; patterns of innovation; spatial spillover; common factors; spatial panel econometric model